Extradural meningeal cystic lesion corresponding to type I meningeal cyst in a dog. Issue 4 (19th November 2018) - Tirrito, Federica; Lombardo, Rocco; Matiasek, Kaspar; Rosati, Marco; Cozzi, Francesca
Abstract : An 11‐year‐old spayed female dobermann was referred for progressive general proprioceptive ataxia and tetraparesis. MRI of the cervical spinal cord demonstrated a compressive, extradural, rounded space‐occupying lesion at the C6‐C7 right vertebral arch. The lesion was hypointense on T1‐weighted images and hyperintense on T2‐weighted images. The dog underwent decompressive surgery; a cystic lesion was removed. Histopathological examination revealed an extradural meningeal cyst corresponding to type I meningeal cyst. A few months after surgery, the neurological condition was substantially improved and no further deterioration was revealed one year later. This is the first reported case of type I meningeal cyst in veterinary medicine. Meningeal type I cysts should be a differential diagnosis for large breed dogs with compressive myelopathy and imaging finding of extradural cystic lesions.